More than Elections: Rural Support and Regime Stability in Africa. (10th July 2018) - Rabinowitz, Beth S.
Abstract: It is generally recognized that rural constituents are critical for winning elections. Development economists also recognize the importance of pro-agricultural policies to economic growth. Yet, little attention has been paid to the effect of rural politics on regime stability. Against conventional wisdom, this article argues that leaders who support rural areas and suppress urban demands are better able to stabilize the state and avoid coups. Because Ghana was able to politically stabilize after a period of state decay and five coups, the article presents an in-depth analysis of the tactical decisions made by the Ghanaian head of state who presided over these changes, John Jerry Rawlings. Using process-tracing, the study illustrates the importance of rural coalitions to stability and regime success. Résumé: Il est généralement reconnu que les électeurs ruraux sont essentiels pour gagner des élections. Les économistes du développement reconnaissent aussi l'importance des pros politiques agricoles à la croissance économique. Cependant, peu d'attention a été accordée à l'effet de la politique rurale sur la stabilité d'un régime. Nonobstant de la sagesse conventionnelle, cet article fait valoir que les dirigeants qui soutiennent les zones rurales et suppriment les exigences urbaines sont mieux en mesure de stabiliser l'État et d'éviter les renversements politiques. Étant donné que le Ghana a été capable de se stabiliser politiquement après une période d'affaiblissement de l'État et cinq renversements, cet article présente une analyse approfondie des décisions tactiques prises par le ghanéen chef d'État qui a présidé à ces changements, John Jerry Rawlings. À l'aide d'un processus de traçage, cette étude illustre l'importance des coalitions rurales à la stabilité et au succès du régime.